Studi Tentang Kebijakan Upah Minimum Regional di Propinsi Jawa Tengah - Dyah Lukisari (Magister Administrasi Publik, 1999)
The main policy problem of labor and manpower in Indonesian provinces, as exemplified by the case study in Central Java Province, is the the low rate of Regional Minimum Wage (UMR). The UMR policy are decided through negotiations among three institutions: labor unions, enterpreneur groups, and the government. The bargaining power of labor unions is very much depended upon the internal cohession of its members, meanwhile of the enterpreneur groups are relatively in better positions as they could deal with governmental policy makers by giving rewards through their economic resources. Government officials, who are supposed to back employees, have not played their role as most of them did not act as a good mediator of the conflicts. , Unfortunately, as most of the NGOs are still easily co-opted by the bueaucratic policy makers and the media have not given enough concern to the labor issues, policies regarding UMR do not always help the employees. It can be concluded, therefore, that the low UMR rate in Central Java is caused by patrimonial political culture in the bureaucracy as evidenced in a